Unveiling the Influence of User-Generated Content on Tourist Destination Choice: Insights from Moroccan Travel Experiences - SALAMI , Salima; MOUKRIM , Anas; DIOUCH , Younes; GABER , Hasna (Revue Internationale des Sciences de Gestion, 2023)
This study explores the impact of User-Generated Content (UGC) on local tourists' decision- making when choosing Morocco as their travel destination. It examines factors such as perceived value, enjoyment, risks, and privacy concerns. The research involves in-depth interviews with 10 tourists who have visited Morocco. The study examines how tourists use UGC to plan their trips, their perceptions of information on social media and online review sites, and the broader impacts of UGC on their travel experiences. The findings offer valuable insights into the role of UGC in shaping destination choices and offer practical implications for improving the overall tourist experience in Morocco's tourism industry.